2016
DOI: 10.1177/1054773814565174
|View full text |Cite
|
Sign up to set email alerts
|

Experiences With Family Health Conversations at Residential Homes for Older People

Abstract: The aim of this study was to highlight family members' experiences of participating in Family Health Conversation (FamHC), based on families in which a family member was living in a residential home for older people. A total of 10 families and 22 family members participated in evaluating family interviews 1 month after participating in FamHC. The interviews were analyzed by qualitative content analysis. The main finding was being a part of FamHC increased family members' insights, understanding, and communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 35 publications
2
24
1
Order By: Relevance
“…Also, previous studies have shown that families participating in FamHC have improved insight, understanding and communication. Thus, negative feelings could be expressed openly and reflected upon within the family (17,(31)(32)(33)(34)(35). Also, a study by Sundin et al (36) shows that family members share their beliefs and talk about serious issues.…”
Section: Discussionmentioning
confidence: 99%
“…Also, previous studies have shown that families participating in FamHC have improved insight, understanding and communication. Thus, negative feelings could be expressed openly and reflected upon within the family (17,(31)(32)(33)(34)(35). Also, a study by Sundin et al (36) shows that family members share their beliefs and talk about serious issues.…”
Section: Discussionmentioning
confidence: 99%
“…Research into FamHc shows positive impact for families [19-22, 30-32]. Based on the increased evidence in the literature on positive outcomes of paying attention to families in health care, FamHC may facilitate building a trusting relationship with families that have a family member living in a residential home.…”
Section: Introductionmentioning
confidence: 99%
“…[28] It might be that these new and positive ways of communicating were kept in their own dialogues within the family after the intervention was concluded. Also, Dorell et al [26] have shown within the context of residential care, that one month after participating in FamHC there was an increase in the communication within the family. An increased quality in family communications has also been found in other studies on family systems nursing interventions.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Empirical studies revealing effects and responses after participating in FamHC are, however, still scarce, but the intervention has started to be evaluated from various angles. [25][26][27][28][29] From these studies, FamHC has been described as a successful conversation with a possible working mechanism in which narrating, listening and reconsidering in interaction support family health. The FamHCs mediate understanding of multiple ways of being and acting, see new possibilities and developing new meanings and hope to make the situation manageable.…”
Section: Family Supportmentioning
confidence: 99%